2014
DOI: 10.1136/bmjopen-2014-005781
|View full text |Cite
|
Sign up to set email alerts
|

Individualising dual antiplatelet therapy after percutaneous coronary intervention: the IDEAL-PCI registry

Abstract: ObjectiveTo evaluate the clinical utility of individualising dual antiplatelet therapy (DAPT) after percutaneous coronary intervention (PCI) in an all-comers population, including ST-elevation myocardial infarction (STEMI) patients.SettingTertiary care single centre registry.Participants1008 consecutive PCI patients with stent implantation, without exclusion criteria.InterventionPeri-interventional individualisation of DAPT, guided by multiple electrode aggregometry (MEA), to overcome high on-treatment platele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 29 publications
1
19
1
1
Order By: Relevance
“…This recurrence has been associated with high on-treatment platelet reactivity (HPR), with up to more than 60% of subjects being reported to be resistant to antiplatelet therapy (aspirin or clopidogrel) [17, 18]. Although some studies showed a link between HPR and major adverse vascular events [19, 20], the use of platelet function analysis to detect and manage HPR continues to be debated. Most studies that investigated HPR were undertaken for patients already receiving antiplatelet therapy without assessing baseline platelet reactivity [19, 20], which may partly explain the conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…This recurrence has been associated with high on-treatment platelet reactivity (HPR), with up to more than 60% of subjects being reported to be resistant to antiplatelet therapy (aspirin or clopidogrel) [17, 18]. Although some studies showed a link between HPR and major adverse vascular events [19, 20], the use of platelet function analysis to detect and manage HPR continues to be debated. Most studies that investigated HPR were undertaken for patients already receiving antiplatelet therapy without assessing baseline platelet reactivity [19, 20], which may partly explain the conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods of laboratory assessment of platelet aggregation were used with the MEA Multiplate method repeatedly showing consistent results across several studies [20, 35, 57]. …”
Section: Discussionmentioning
confidence: 99%
“…The Multiplate will measure the platelet activity (defined as aggregation capability after activation with Adenosine diphosphate [ADP]) as an area under the curve reported in area units over time (AU*min). Platelet hyper-reactivity is defined based on the manufacturer's recommendations and published data, with a cut-off of 50 AU*min for ADP-induced aggregation (24).…”
Section: Discussionmentioning
confidence: 99%
“…After the study data is collected, the patient identification will be encoded, and only the investigator will have access to this information, in accordance with Good Clinical Practice and Helsinki declaration of patient confidence (24). The collected data will be entered electronically in a Research Electronic Data Capture management system (REDCap).…”
Section: Data Managementmentioning
confidence: 99%